The Portuguese S3-Non-invasive Ventilation (S3-NIV) questionnaire for home mechanically ventilated patients - Ribeiro, C (2021)
Short, valid and easy to use tools are needed to monitor home mechanical ventilation (HMV) in clinical practice and for organization of HMV services. The S3NIV is a self-administered questionnaire containing 11 items that includes a Respiratory Symptoms and Sleep & Side Effects subscores, ranging from 0 (highest impact of disease and treatment) to 10 (lowest impact of disease and treatment). The Portuguese version of the questionnaire was obtained using translation-back translation process with two professional translators and it was then validated on 234 stable patients (128 male patients, 53.8%) with a mean age of 69.3 (SD 11.0) years under long-term home non-invasive ventilation. Data on total score and subscales according to disease category are reported on the table. Internal consistency for the total score was good (Cronbach’s α coefficient of 0.76) as well as for the Respiratory Symptoms and the Sleep & Side effects domains (Cronbach’s α coefficient=0.68 and Cronbach’s α coefficient=0.72, respectively). The Portuguese version of the S3-NIV questionnaire is a simple and valid tool for the routine clinical assessment of patients receiving HMV. Although they have advanced diseases, it appears patients recognize treatment benefits and have controlled side effects.